The heroine with 1,001 faces - Tatar, Maria, 1945- (Liveright Publishing Corporation, 2021)
"The Heroine with 1,001 Faces dismantles the cult of warrior heroes, revealing a secret history of heroinism at the heart of our collective cultural imagination. Here, Maria Tatar, a leading authority on fairy tales and folklore, explores how heroines, rarely wielding a sword and often deprived of a pen, have flown beneath the radar even as they have been bent on redemptive missions. Deploying the domestic crafts and using words as weapons, they have found ways to survive assaults and rescue others from harm, all while repairing the fraying edges in the fabric of their social worlds. Like the tongueless Philomela, who spins the tale of her rape into a tapestry, or Arachne, who portrays the misdeeds of the gods, they have discovered instruments for securing fairness in the storytelling circles where so-called women's work -- spinning, mending, and weaving -- is carried out. Tatar challenges the canonical models of heroism in Joseph Campbell's The Hero with a Thousand Faces, with their male-centric emphasis on achieving glory and immortality. Finding the women missing from his account and defining their own heroic trajectories is no easy task, for Campbell created the playbook for Hollywood directors. Audiences around the world have willingly surrendered to the lure of quest narratives and charismatic heroes. Whether in the form of Frodo, Luke Skywalker, or Harry Potter, Campbell's archetypical hero has dominated more than just the box office. In a broad-ranging volume that moves with ease from the local to the global, Tatar demonstrates how our new heroines wear their curiosity as a badge of honor rather than a mark of shame, and how their 'mischief making' evidences compassion and concern. From Bluebeard's wife to Nancy Drew, and from Jane Eyre to Janie Crawford, women have long crafted stories to broadcast offenses in the pursuit of social justice. Girls, too, have now precociously stepped up to the plate, with Hemione Granger, Katniss Everdeen, and Starr Carter as trickster figures enacting their own forms of extrajudicial justice. Their quests may not take the traditional form of a 'hero's journey,' but they reveal the value of courage, defiance, and above all, care." --